De la production sociale de la ville à la production de vulnérabilités, l’exemple de la ville de Djibouti - Amina Said Chiré (Territoire en Mouvement)
The article analyzes how the development of the city of Djibouti generates social vulnerability factors for a large share of its inhabitants. To achieve this goal, it tests the relevance of a dimensional approach to tackle the social, political and economic procedures through which the production of the city generates vulnerabilities’ factors. The main postulates defended are based partly on the role of socio-spatial inequalities in the city and playing key roles in the construction of vulnerability to natural and man-made hazards. On the other hand, they are based on the deep reasons explaining the exclusion and marginalization of some as the conditions for reducing the vulnerability of others, especially for the state. In this sense, the past legacies of urban and economic policies are questioned to tackle the social and spatial determinants of vulnerabilities. The results obtained seem to go beyond this contribution: the socio-spatial inequalities are responsible for the construction of social vulnerability factors in Djibouti for the poor but also for the state.